2005-06 Farm Bill Survey: Characteristics of Florida Producers Who Participated - Rodney L. Clouser (EDIS)
FE663, a 4-page fact sheet by Rodney L. Clouser, is one of four fact sheets reporting information collected from Florida producers concerning attitudes and views regarding U.S. Congressional enactment of the next farm bill. This fact sheet reports on the socioeconomic characteristics of Florida farm producers completing the survey. Published by the UF Department of Food and Resource Economics, October 2006.